Dissecting the potential role of hepatitis E virus ORF1 nonstructural gene in cross‐species infection by using intergenotypic chimeric viruses. Issue 12 (11th July 2020) - Tian, Debin; Yugo, Danielle M.; Kenney, Scott P.; Lynn Heffron, C.; Opriessnig, Tanja; Karuppannan, Anbu K.; Bayne, Jenna; Halbur, Patrick G.; Meng, Xiang‐Jin
Abstract: Hepatitis E virus (HEV) infects humans and more than a dozen other animal species. We previously showed that open reading frame 2 (ORF2) and ORF3 are apparently not involved in HEV cross‐species infection, which infers that the ORF1 may contribute to host tropism. In this study, we utilize the genomic backbone of HEV‐1 which only infects humans to construct a panel of intergenotypic chimeras in which the entire ORF1 gene or its functional domains were swapped with the corresponding regions from HEV‐3 that infects both humans and pigs. We demonstrated that the chimeric HEVs were replication competent in human liver cells. Subsequently, we intrahepatically inoculated the RNA transcripts of chimeras into pigs to determine if the swapped ORF1 regions confer the chimeras' ability to infect pigs. We showed that there was no evidence of infectivity in pigs for any of the chimeras. We also investigated the role of human ribosome protein sequence S17, which expanded host range in cultured cells, in HEV cross‐species infection. We demonstrated that S17 insertion in HEV ORF1 did not abolish HEV replication competency in vitro, but also did not expand HEV host tropism in vivo. The results highlight the complexity of the underlying mechanism of HEV cross‐species infection. Highlights: Four intergenotypic chimeric HEVs in the backbone of HEV‐1 containing ORF1 or its functional domains from HEV‐3 were replication‐competent in vitro. A recombinant HEV in the backbone of HEV‐1 with insertion of human ribosome protein sequence S17 in the ORF1 was replication‐competent in cultured liver cells. The four chimeric HEVs and the recombinant HEV failed to experimentally infect pigs. The ORF1 alone is probably not involved in HEV host tropism.